Our man in Mexico : Winston Scott and the hidden history of the CIA - Morley, Jefferson (University Press of Kansas, 2008)
In this book, the author reveals how Winston Scott ran hundreds of covert espionage operations from his headquarters in the U.S. Embassy while keeping three Mexican presidents on the agency's payroll, participating in the Bay of Pigs fiasco, and, most intriguingly, overseeing the surveillance of Lee Harvey Oswald during his visit to the Mexican capital just weeks before the assassination of President Kennedy. The author reveals the previously unknown scope of the agency's interest in Oswald in late 1963, identifying for the first time the code names of Scott's surveillance programs that monitored Oswald's movements. He shows that CIA headquarters cut Scott out of the loop of the agency's latest reporting on Oswald before Kennedy was killed. He documents why Scott came to reject a key finding of the Warren Report on the assassination and how his disillusionment with the agency came to worry his longtime friend James Jesus Angleton, legendary chief of CIA counterintelligence. Angleton not only covered up the agency's interest in Oswald but also, after Scott died, absconded with the only copies of his unpublished memoir. Interweaving Win Scott's personal and professional lives, the author has crafted a real-life thriller of Cold War intrigue - a compelling saga of espionage that uncovers another chapter in the CIA's history.